Joint Press Statement of the CGIAR and CAADP-XP4 Partners: African Research and Innovation Partners Synergize to Accelerate Agricultural Knowledge Scaling - Abugri, Benjamin; Victor, Michael (Centre for Coordination of Agricultural Research and Development for Southern Africa, 2024)
Addis Ababa, Ethiopia — December 13, 2024 — The CGIAR and CAADP-XP4 Partners successfully concluded the "Second Workshop to Operationalize the African Agricultural DSpace Repository" at the ILRI Campus in Addis Ababa, Ethiopia. This three-day event, held from December 11 to 13, brought together Knowledge Management Officers, IT and web developers from CAADP-XP4 Partners (FARA, CCARDESA, AFAAS, CORAF, and ASARECA) alongside CGIAR experts led by the International Livestock Research Institute (ILRI). The workshop reinforced partnerships and took concrete steps toward advancing the African Agricultural Research Information and Innovation Space (AARIISpace).